Identifying dopamine supersensitivity through a randomized controlled study of switching to aripiprazole from other antipsychotic agents in patients with schizophrenia. (January 2022) - Ma, Chia-Hao; Chan, Hung-Yu; Hsieh, Ming H.; Liu, Chen-Chung; Liu, Chih-Min; Hwu, Hai-Gwo; Kuo, Ching-Hua; Chen, Wei J.; Hwang, Tzung-Jeng
Background: Aripiprazole has been reported to worsen psychotic symptoms when switching from other antipsychotics, possibly due to dopamine supersensitivity psychosis. Objective: This study aimed to explore the predictors and possible underlying mechanisms of aripiprazole-related psychotic exacerbation. Methods: We conducted an 8-week, open-label, randomized controlled study from October 2007 to September 2009, assigning patients with a primary diagnosis of schizophrenia or schizoaffective disorder to switch from other antipsychotics to aripiprazole with 2-week dual administration, and then to taper off the original agents in fast (n = 38, within 1 week) or slow (n = 41, within 4 weeks) strategies. Positive and Negative Syndrome Scale (PANSS) was examined at day 0, 7, 14, 28, 56. Aripiprazole-related exacerbation (ARE) was defined positive as a 2-point increase in delusion/hallucination dimension score within 28 days compared with baseline. Baseline demographic, clinical and intervention-related variables were compared between the ARE+ and ARE- groups. Results: Of the 79 randomized patients, 21 fulfilled the criteria of ARE+, and 46 were classified as ARE-. Fourteen patients in the ARE+ group had worsening psychotic symptoms in the first and second weeks. Compared with the ARE- group, the ARE+ group had a higher baseline chlorpromazine equivalent dose (405.8 ± 225.8 mg vs 268.1 ± 165.4 mg, p  = 0.007) and was associated with prescription of first-generation antipsychotics ( p  = 0.038). Conclusions: A higher dose of original antipsychotics and prescription of first-generation antipsychotics may be associated with a higher risk of ARE. The underlying mechanism might be covert dopamine supersensitivity psychosis. These findings may help to identify high-risk patients and guide appropriate treatment strategies. Trial Registration: ClinicalTrials.gov, identifier: NCT00545467